"Soos 'n hamer wat 'n rots vermorsel": die Afrikaanse Bybel van 1933 as vertaling - J. A. Naudé (Acta Theologica)
The first complete Bible translation in Afrikaans was published in 1933. This article describes and analyses this translation. Given the new developments in translation studies, one should not evaluate a translation normatively, but rather describe it. Any new translation constructs a domesticated representation of a foreign text and culture, which simultaneously keeps intelligibility and ideology in mind. The representation refers to the linguistically inscribed preferences regarding the selection and construction of discourses in the Bible translation. The 1933 translation is analysed and explained in terms of the formation of particular cultural, political and religious identities. Some of the fixed perceptions of the 1933 translation are revisited by dealing with issues like the context of the translation, its source text, the translation team, the translation process and the sociocultural impact of the translation.